2022
DOI: 10.1039/d2cc00292b
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis and hydrolytic stability of cyclic phosphatidic acids: implications for synthetic- and proto-cell studies

Abstract: Cyclic phosphatidic acids (cPAs) are bioactive compounds with therapuetic potential, but are in short supply. We describe a robust synthesis of cPAs employing an efficient cyclophosphorylation procedure and report on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…This difference may result from the involvement of other LPA-producing enzymes such as GDE4 and acylglycerol kinase 31 since MCF-7 cells have poor ATX expression 32 . It is also possible that cPA was hydrolyzed to LPA non-enzymatically in the presence of water 33 . Alternatively, it is possible that cPA produced by GDE7 is converted to β-LPA since it has been reported that cPA produced by ATX is converted to β-LPA 34 .…”
Section: Discussionmentioning
confidence: 99%
“…This difference may result from the involvement of other LPA-producing enzymes such as GDE4 and acylglycerol kinase 31 since MCF-7 cells have poor ATX expression 32 . It is also possible that cPA was hydrolyzed to LPA non-enzymatically in the presence of water 33 . Alternatively, it is possible that cPA produced by GDE7 is converted to β-LPA since it has been reported that cPA produced by ATX is converted to β-LPA 34 .…”
Section: Discussionmentioning
confidence: 99%
“…This difference may result from the involvement of other LPA-producing enzymes such as GDE4 and acylglycerol kinase 23 since MCF-7 cells have poor ATX expression 24 . It is also possible that cPA was hydrolyzed to LPA non-enzymatically in the presence of water 25 . In humans, GDE7 is abundant in the kidney, prostate, ovary, and placenta 13 , while PLD2 is widely expressed in various tissues 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of cyclophospholipids followed previous reports. , Briefly, to a solution of monocaprin (1.0 mmol) or monoolein (1.0 mmol) in 2 mL of N -methyl-2-pyrrolidone (NMP) was added 2–3 mmol of bis­(dimethylamino) phosphorodiamidate (BDMDAP, 2 mmol of CPC10, and 3 mmol of CPC18) and dimethyltin dichloride (C 2 H 6 Cl 2 Sn) (0.2 mmol for CPC10 and 0.3 mmol for CPC18) (Figure S22A). The reaction was subjected to a microwave (120 °C, normal power) for 30 min.…”
Section: Methods and Experimental Sectionmentioning
confidence: 99%
“…The cyclophospholipids were purified through successive liquid− liquid extractions, as previously described (Figure S22A). 71 CPC10 was also synthesized in a single step starting with 2.1 mmol monocaprin as depicted in Figure S21A. 63 For CPC18, Na + counterions were exchanged with diethylaminoethyl (DEAE) anion exchange chromatography and eluted with 1 M triethylammonium in water.…”
Section: Methods and Experimental Sectionmentioning
confidence: 99%